Effect Of Mentha Piperita On Biochemical Parameters Of Broilers Fed Ochratoxin - Nayak, Anju; Joseph, E.; Nayak, S.; Swamy , M.; Baghel , R.P.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A trial was conducted to study the effect of Mentha piperita on broilers fed ochratoxin. The results of the present study reveals that feeding of ochratoxin at both the levels (2 and 4 ppm) significantly (P
Keywords: Mentha piperita; biochemical parameters; ochratoxin